PENGARUH LATIHAN LADDER DRILL (ALI SHUFFLE) TERHADAP KELINCAHAN ANGGOTA CLUB BASKET ANGKASA U18 PEKANBARU - Indah Putri Mentari; Slamet '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on my observation to the member of Angkasa Basketball U18 Pekanbaru, it seemed that the agility of the member was not maximal. It seemed that the member was slow to move in finding the location, difficult to pass the enemy when bringing the ball, and difficult to follow or block the enemy in deffense. Because the researcher wanted to increase the agility of Angkasa Basketball U18 Pekanbaru, the researcher would give the appropriate treatment. The purpose of the research was to see the effect of ladder drill (ali shuffle) through the agility of Angkasa Basketball U18 Pekanbaru. The population was 12 people of Angkasa Basketball players U18 Pekanbaru. The collecting data technique was total sampling based on Ari Kunto’s statement (2006 : 134) if the population was less than 100 people. The instrument of the research was the agility test by using pree test and post test illinois agility run test. The data was analysed by using T test. According to T test, it was Tcount 6.671 > 1,796 (Ttable), so the hyphothesis was accepted. It meant that there was a significant effect of ladder drill (ali shuffle) through the agility of Angkasa Basketball U18 Pekanbaru. If there was a difference score between pree test and post test in the amount of 0.48, it showed that the ladder drill (ali shuffle) through the agility of the members gave a better change in the amount of 2.95 % compared it before the treatmentKeywords : Ladder Drill (Ali Shuffle) through the agility